Nanostructure and its effect on electrochemical properties of polyanionic Li2CoSiO4 for lithium ion batteries. (23rd July 2020) - Du, Wenqiang; Tian, Ailing; Zhang, Ying; Chen, Zhenlian; Zhang, Zhifeng; Wang, Deyu; Li, Jun
Abstract: This work reports a facile strategy to synthesize carbon-coated Li2 CoSiO4 /C particles with rich nanostructures by a two-step scheme starting with a low-temperature hydrothermal method. The size and morphology of particle aggregates can be regulated by the (OH − ) concentration and viscosity of the precursor solution, a mixture of ethylene glycol and deionized water, for the hydrothermal synthesis. In addition to the good electrical conductivity from the carbon coating, the size of the primary nanoparticles and the mesopore associated with the aggregations play an important role in improving the electrochemical properties of polyanionic Li2 CoSiO4 . The low-dimensional belt-like and sheet-like Li2 CoSiO4 /C nanomaterials present a higher reversible capacity 136.6 mAh g −1 and 147 mAh g −1, respectively, in the first charging–discharging cycle between 2 V and 4.6 V. XRD, SEM/TEM, and EDS are used to characterize the crystalline structure and aggregation patterns. TGA and Raman spectra are employed to analyze the carbon coating on different morphologies. The analysis of electrochemical impedance spectroscopy highlights the critical role of the interface between the electrolyte and particles. This study provides insights into the rational design and synthesis of high-performance polyanionic cathodes including silicates.